2022
DOI: 10.1002/macp.202200045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methacrylic Acid in PNNPAM Microgels on the Catalytic Activity of Embedded Palladium Nanoparticles

Abstract: Poly-N-n-propylacrylamide based microgels with embedded Pd-nanoparticles are synthesized with varying amounts (5-25 mol%) of methacrylic acid (MAc) comonomer. The microgels are characterized to investigate the influence of the comonomer content on catalytic activity of the hybrid particles. Since the acidity changes significantly upon copolymerization, the incorporated amount and apparent p K a value of the MAc via potentiometric titration are determined. The thermoresponsive properties of the microgels are ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…So, the HDD of hybrid microgels does not increase, and reactant molecules are facing difficulty during diffusion. Similar behavior of palladium nanoparticles loaded in microgels for catalytic reduction of 4NiP was reported by Sabadasch et al [65]. Similarly, Thomas et al [26] have reported the catalytic activity of amino groups containing hybrid microgels for the reduction of 4NiP under different pH values.…”
Section: As a Catalystsupporting
confidence: 77%
See 1 more Smart Citation
“…So, the HDD of hybrid microgels does not increase, and reactant molecules are facing difficulty during diffusion. Similar behavior of palladium nanoparticles loaded in microgels for catalytic reduction of 4NiP was reported by Sabadasch et al [65]. Similarly, Thomas et al [26] have reported the catalytic activity of amino groups containing hybrid microgels for the reduction of 4NiP under different pH values.…”
Section: As a Catalystsupporting
confidence: 77%
“…The effect of this behavior gradually decreases with increasing acidic group-containing co-monomers. For example, Sabadasch et al [65] have reported the synthesis of palladium nanoparticles loaded in poly(N-n-propylacrylamide-methacrylic acid) P(NNA-MeAA) and studied the swelling and de-swelling behavior under various concentrations of MeAA in microgels. They synthesized the microgels using 5 mol% to 25 mol% of MeAA.…”
Section: Anionic Microgels and Hybrid Microgelsmentioning
confidence: 99%
“…The smart, adaptive microgels have high potential in various fields for applications in catalysis (8,9), in uptake and release (10), in tissue engineering (11,12), as sensors (13,14), for advanced bioimaging (15), as photonic materials (16,17), in extraction processes (18), as responsive membranes (19,20), and as antifouling surface coatings (21). Apart from the numerous medical and technical applications, responsive microgels are also powerful materials to investigate basic physics in colloidal matter (22,23).…”
Section: Introductionmentioning
confidence: 99%